Prevalence, diversity and antimicrobial resistance of Salmonella enterica and Pseudomonas aeruginosa isolates from spring water in a rural area of northwestern Morocco - Ilham Nassri; LATIFA TAHRI; AMAL SAIDI; NAJIA AMEUR; MOHAMMED FEKHAOUI (Society for Indonesian Biodiversity, 2021)
Abstract. Nassri I, Tahri L, Saidi A, Ameur N, Fekhaoui M. 2021. Prevalence, diversity and antimicrobial resistance of Salmonella enterica and Pseudomonas aeruginosa isolates from spring Water in a rural area of northwestern Morocco. Biodiversitas 22: 1363-1370. The persistence and diversity of serotypes belonging to pathogens in environmental waters including surface and groundwater have been widely documented and that the aquatic environment represents a relatively stable environment for these microorganisms. Study was carried out on the prevalence, diversity, and antibiotic resistance of Salmonella enterica and Pseudomonas aeruginosa isolates taken from 102 samples of spring water in a rural region of Northwestern Morocco (Rabat-Salé-Zemour-Zaer) collected for two seasonal campaigns between March 2010 and June 2011. The search and identification of S. enterica and P. aeruginosa were carried out according to ISO 19250 and ISO 16266 methods respectively. The serotyping of S. enterica and P. aeruginosa was carried out according to the Kauffmann and White and IATS (International Antigenic Typing System) schemes respectively. Antibiotic resistance of S. enterica and P. aeruginosa were carried out by the Mueller-Hinton agar diffusion method (Biorad). S. enterica showed a prevalence of 10.7% with 09 different serotypes circulating including S. paratyphi B, S. brandenburg, S. kentucky, S. group III b (serotype 50: z52: z53,), S. boon, S. tshiongwe, S. assinie, S. togo, and S. tanger. In contrast, P. aeruginosa showed a prevalence of 21.6% with 07 different serotypes circulating including O6, O1, O7, O9, O4, O3, and O10. In this study, antimicrobial resistance revealed that all isolated strains of S. enterica and P. aeruginosa still exhibit a wild resistance phenotype. Contaminated water sources are reservoirs of these pathogens but do not yet present the risk factors for these bacteria to develop antibiotic resistance.